2016
DOI: 10.1139/bcb-2015-0149
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid and docosahexaenoic acid increase the degradation of amyloid-β by affecting insulin-degrading enzyme

Abstract: Omega-3 polyunsaturated fatty acids (PUFAs) have been proposed to be highly beneficial in Alzheimer's disease (AD). AD pathology is closely linked to an overproduction and accumulation of amyloid-β (Aβ) peptides as extracellular senile plaques in the brain. Total Aβ levels are not only dependent on its production by proteolytic processing of the amyloid precursor protein (APP), but also on Aβ-clearance mechanisms, including Aβ-degrading enzymes. Here we show that the omega-3 PUFAs eicosapentaenoic acid (EPA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 59 publications
3
41
0
Order By: Relevance
“…Accordingly, mutations in PS1 causing FAD showed increased SMase activity (131). Under pathological conditions, high A42 concentrations resulting in oligomers, protofibrils, and fibrils and leading to oxidative stress and inflammatory mechanisms have been demonstrated to additionally activate nSMase (135,136). Similar results have been found by Jana and Pahan (137,138), showing that fibrillary A peptides activate nSMases via NADPH oxidase-mediated mechanisms finally leading to the loss of neurons.…”
Section: Smsupporting
confidence: 65%
“…Accordingly, mutations in PS1 causing FAD showed increased SMase activity (131). Under pathological conditions, high A42 concentrations resulting in oligomers, protofibrils, and fibrils and leading to oxidative stress and inflammatory mechanisms have been demonstrated to additionally activate nSMase (135,136). Similar results have been found by Jana and Pahan (137,138), showing that fibrillary A peptides activate nSMases via NADPH oxidase-mediated mechanisms finally leading to the loss of neurons.…”
Section: Smsupporting
confidence: 65%
“…The obtained result suggested that AKO exerted neuroprotective effect by inhibiting Aβ production or promoting Aβ clearance, which might be due to the high proportion of EPA and DHA. Previous studies had shown that EPA could increase Aβ‐degradation by improving insulin‐degrading enzyme activity (Grimm et al., ). Moreover, dietary DHA reduced Aβ level by reducing presenilin‐1 steady‐state level (Green et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, there have been many reports that docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) relate closely to brain functions (Grimm et al, 2016, Hopperton et al, 2016, Ren et al, 2017). Scallop-derived Pls used in the present study presumably contained relatively large amounts of DHA and EPA (Kraffe et al, 2004, Hanuš et al, 2009).…”
Section: Discussionmentioning
confidence: 99%